An empirical competence-capability model of supply chain innovation - Mandal, Santanu (Business: Theory and Practice, 2016)
Supply chain innovation has become the new pre-requisite for the survival of firms in developing capabilities and strategies for sustaining their operations and performance in the market. This study investigates the influence of supply and demand competence on supply chain innovation and its influence on a firm’s operational and relational performance. While the former competence refers to production and supply management related activities, the latter refers to distribution and demand management related activities. The current investigation further explores how well supply chain management processes are internally executed by the firm’s employees i.e. process compliance is observed as an enabler (moderator) on the relationship between supply chain competences and supply chain innovation. Further the model also explores the moderating influence of environmental uncertainty on the linkage between supply chain innovation and firm performance. The model is empirically validated based on perceptual data collected from 166 supply chain professionals through web based survey. Implications for both managers as well as practitioners are also provided.